Some results of comparison between numerical and analytic solutions of the one-line model for shoreline change - Hoan, Le Xuan (Vietnam Journal of Mechanics, 2006)
A qualitative understanding of the basic properties of complicated physical phenomena can often is obtained through the study of analytic solutions derived from simplified problems. Analytic solutions of shoreline change model for simple shoreline configurations are derived under idealized wave conditions. Both analytic and numerical methods are based on the one-line theory of shoreline change. In this paper some results of comparison of the numerical with analytic solutions are presented